Anencephaly in Mexican Population: A Case Report and Review of Literature [16M]. (May 2016) - Alcantara, Isamarie; Rezai, Shadi; Henderson, Cassandra; Mercado, Ray
Abstract : INTRODUCTION: Anencephaly is the absence of major malformation of the brain, scalp and cranial vault. Neural tube defect occurs between 23rd to 26th days after conception resulting from failed closure of frontal end of the neural tube. Numerous risk factors have been associated with development of Neural Tube Defects (NTD). These risk factors are multifactorials that combine an interaction between genetic, environmental, low socioeconomic status, member of racial or ethnic minority group or folic acid deficiency. METHODS: Case Report. We present a case of a 32 year old Mexican female, G4P2022 with history of two pregnancies that resulted both in anencephalic fetuses. We reviewed the risk factors for the index case and present a systematic literature review of anencephaly. RESULTS: DISCUSSION: Folic acid deficiency, maternal low socioeconomic status, genetics, hereditary predispositions, Hispanic origin, especially Mexicans are some of the risk factors for development of anencephaly. Mexico has one of the highest incidence of anencephaly in the world with a rate of 13.34 per 10, 000 births. Our patient was originally from Puebla, one of the most affected regions of the Mexico, supporting the genetic predisposition of this condition when other risk factors are not present. CONCLUSION: This case is an example of a vulnerable population for development of anencephaly. It highlights the importance of primary and secondary preventive strategies that can be targeted to these groups, including preconceptional counseling and adoption of measures to prevent NTD and the need of additional research to evaluate the genetic, socioeconomic and environmental factors predisposing NTD.